2013
DOI: 10.1021/jp4000957
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Seebeck Effects by Using Excited States in Organic Semiconducting Polymer MEH-PPV Based on Multilayer Electrode/Polymer/Electrode Thin-Film Structure

Abstract: This article reports the experimental studies on using photoexcitation-generated excited states as a new approach to increase Seebeck coefficient as well as electrical conductivity in an organic semiconducting polymer MEH-PPV (poly(2-methoxy-5-(2′-ethylhexyloxy)-p-phenylene vinylene) with multilayer electrode/polymer/electrode thin-film architecture. Our experimental results show that a photoexcitation can lead to a large Seebeck coefficient of 305 μV/K in the ITO/MEH-PPV/Au device under the light intensity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…In addition, we find the undoped perovskite thin film possesses negative Seebeck coefficient under 35 °C; when the temperature was increased from 35 to 70 °C, the Seebeck coefficient shows positive value. As perovskite plays a role of n‐type semiconductor as well of p‐type semiconductor, the controlling phase transition temperature acts as an effective way to modulate the electronic and thermoelectric properties . The Bi‐doped MAPbI 3 films exhibit positive Seebeck coefficient from 30 to 70 °C, which means the majority charge carrier of Bi‐doped MAPbI 3 carrier is hole.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we find the undoped perovskite thin film possesses negative Seebeck coefficient under 35 °C; when the temperature was increased from 35 to 70 °C, the Seebeck coefficient shows positive value. As perovskite plays a role of n‐type semiconductor as well of p‐type semiconductor, the controlling phase transition temperature acts as an effective way to modulate the electronic and thermoelectric properties . The Bi‐doped MAPbI 3 films exhibit positive Seebeck coefficient from 30 to 70 °C, which means the majority charge carrier of Bi‐doped MAPbI 3 carrier is hole.…”
Section: Resultsmentioning
confidence: 99%
“…At low temperature, the Seebeck voltage produced by thermally assisted charge transport mainly comes from entropy difference, but at high temperature, it comes simultaneously from entropy as well as polarization which is both beneficial for enhanced Seebeck coefficient and carrier transport. [16a,18]…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the electrical conductivity and Seebeck coefficient generated from the ITO/P3HT/Au device under illumination, with PCBM doping content of 10%, 20%, 30%. We have previously researched the thermoelectric properties of single p‐type and n‐type thermoelectric devices under dark conditions and showed that the thermoelectric properties are better under illumination than in dark conditions. Therefore, here we have only studied the device thermoelectric properties under illumination conditions.…”
Section: Resultsmentioning
confidence: 99%
“…During the Seebeck measurements, the ITO substrate is heated, and the unheated side is cooled using a fan to maintain a constant temperature. In our previous research , we used the light intensity of 8, 12, 16 mW/cm 2 , and we knew that the Seebeck coefficient and electrical conductivity increased as the light intensity increased. To ensure consistent results here we selected light intensity of 16 mW/cm 2 using a filament lamp.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is required to use V 2 O 5 in conjunction with another nanostructured material possessing higher electronic conductivity. [27][28][29][30] For example, Chen et al constructed the MWCNT-V 2 O 5 core-shell sponge for high power density. 31 Zhang et al fabricated carbon-coated V 2 O 5 with high performance.…”
Section: Introductionmentioning
confidence: 99%